Peningkatan Kreativitas Siswa SMP Wisata Sanur Melalui Penerapan Model Pembelajaran Group Investigation (GI) Berbasis Media Mind Mapping: Improving Creativity of Students of Sanur Wisata Junior High School Through The Application of Group Investigation (GI) Learning Model Based on Mind Mapping Media - Dewa Ayu Sri Ratnani (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2019)
This study aims to analyze whether the application of Group Investigation (GI) learning model Based on Mind Mapping media can improve creativities of the student of SMP Wisata Sanur. The research type is Pre-Exprimental Design with One-group Pretest-Postest Designs research design conducted at SMP Wisata Sanur from April to May. Data collection using creativity assessment rubrics with 7 aspects. The result showed that there was an increase of creativity score from 75,3 to 169,2 with significance level of each aspect of creativity, ie Design aspect (p = 0,017), Color (p = 0,017), Idea and Context (p = 0,017), Kata Key (p = 0.018), Combining ideas (p = 0.018), Hierarchy Level (p = 0.017), Presentation Concept (p = 0.017). Based on the data obtained after being tested with Wilcoxon Match Pairs there was a significant difference (p = 0,018> 0,05) on student creativity in making Mind Mapping before and after apply the learning model. The conclusion of this research is the application of cooperative learning model of Group Investigation based on Mind Mapping has an effect on to the creativity of junior high school students of Sanur Tourism. Keywords: Group Investigation, Creativity, Mind Mapping Abstrak. Penelitian ini bertujuan untuk menganalisis apakah penerapan model pembelajaran Group Investigation (GI) Berbasis media Mind Mapping dapat meningkatkan kreativitas siswa SMP Kerta Wisata Sanur. Jenis penelitian adalah Pre-Exprimental Design dengan rancangan penelitian One-group Pretest-Postest Designs yang dilaksanakan di SMP Wisata Sanur . Data didapatkan menggunakan rubrik penilaian kreativitas dengan 7 aspek. Hasil penelitian menunjukkan terdapat peningkatan jumlah skor kreativitas dari 75,3 menjadi 169,2 dengan taraf signifikansi masing-masing aspek kreativitas yaitu aspek Rancangan (p=0,017), Warna (p=0,017), Ide dan Konteks (p=0,017), Kata Kunci (p=0,018), Menggabungkan ide-ide (p=0,018), Tingkat Hirarki (p=0,017), Konsep Presentasi (p=0,017). Hasil uji dengan Wilcoxon Match Pairs terdapat perbedaan yang signifikan (p= 0,018 > 0,05) pada kreativitas siswa dalam membuat Mind Mapping sebelum dan sesudah menerapkan model pembelajaran kooperatif tipe Group Investigation. Kesimpulan dari penelitian ini adalah penerapan model pembelajaran kooperatif tipe Group Investigation berbasis Mind Mapping mampu meningkatkan kreativitas siswa SMP Wisata Sanur. Kata kunci : Group Investigation, Kreativitas, Mind Mapping